The effect of general anaesthesia versus conscious sedation in dosimetric distribution of intracavitary radiotherapy in cervical cancer patients - Rathore, Narendra; Shukla, Arvind Kumar; Bana, Poonam Chand; Jain, Abhay Kumar; Rajpurohit, Vikram Singh; Intodia, Kiran (International Journal of Research in Medical Sciences, 2017)
Background: Majority of Indian patients presents in locally advanced stage and most of them treated by combination of external teletherapy and intracavitary brachytherapy (ICRT). Because of deficient infrastructure, the waiting period is generally long at existing caner canters. Hence ICRT may be done in conscious sedation to treat more patients by avoiding time consuming general anaesthesia. The aim of this study is to know the effect of general anaesthesia vs. conscious sedation in dosimetric distribution in brachytherapy and its feasibility. Methods: Total 80 ICRT applications were randomized to general anaesthesia (GA) and conscious sedation (CS) groups. Fletcher suit type of applicators was used and dose delivery equipment was cobalt 60 high dose rate remote after loading brachytherapy unit. In CS group, injection midazolam 0.5-8mg (median 2.5mg) in the form of slow i.v. infusion was used along with antiemetic support. Results: Total 6 parameters were analyzed. e.g., Dose to point A1, Dose to point A2, Bladder max dose, Bladder mean dose, Rectal max dose and Rectal mean dose. The dose distribution was found similar both groups and it did not depend on type of anaesthesia. Conclusions: The high volume centers of developing countries are most suitable candidate to opt conscious sedation to perform ICRT to treat more cancer cervix patients in same time frame.